A Tool for Accurate Stoichiometric Composition of Cryopreservative Media for Fetal and Induced Pluripotent Stem Cell‐Derived Human Neural Stem Cells. Issue 5 (5th May 2021) - Niles, Walter D.; Snyder, Evan Y.
Abstract: Fetal human neural stem cells (fhNSC) are of considerable interest as potential regenerative therapies for neuronal or glial degeneration or destruction resulting from genetic abnormalities, disease, or injury. Realization of this potential requires securing a supply of cells sufficient to meet the needs of transplantation, which are often tens to hundreds of millions of cells per dose. This challenge necessitates the establishment of safe and efficient cell banking protocols. Cryopreservation, involving the slow freezing or vitrification of cells, enables storage of fhNSC for prolonged periods, while maintaining their viability and multipotency required for clinical use. To optimize cryopreservation of fhNSC, attention has become focused on the composition of the medium used to effect cryopreservation by slow freezing/vitrification—i.e., the cryopreservative medium. The cryopreservative medium is typically specified as a dilution of a concentrated cryoprotectant, such as dimethylsulfoxide or glycerol, in cell culture medium that is often combined with serum or another source of necessary growth factors. The present work is devoted to a computational tool for determining the composition of a cryopreservative medium that can be combined with dissociated fhNSC resuspended in a certain volume of culture medium to achieve the criterion of stoichiometric dilution of cryoprotectant favorable to cell viability in the final mixture of cryopreservative medium and cells. © 2021 Wiley Periodicals LLC. Basic Protocol : Culture and passage of fhNSC, counting of enzymatically dissociated fhNSC, and quantitative formulation of cryomedium Alternate Protocol : Procedure when cell medium is not added to the cryomedium